Addressing Online Fraud And Illegal Gambling As Cross Border Cybercrime Through The Budapest Convention - Nikmah Khairani Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Cross-border cybercrimes like online fraud and illegal gambling surge in Indonesia, inflicting IDR 3.2 trillion losses by mid-2025 due to foreign perpetrators exploiting jurisdictional voids in national laws. This narrative review aims to scrutinize regulatory gaps in Indonesia's ITE Law, KUHP, and KUHAP, alongside Budapest Convention prospects for transnational enforcement. Population encompasses 2015-2025 literature from Scopus, official reports, and ASEAN documents; purposive sample selects 25 key sources on cybercrime trends and cooperation. Instruments include systematic search protocols with keywords